KEBIJAKAN PENOLAKAN PENGUNGSI DI HONGARIA PADA 2015- 2017 - Ashfihani, Evi; Ismiyatun, Ismiyatun (Laporan Penelitian dan Pengabdian Masyarakat, 2024)
This paper aim to analyze the Hungarian Government Policy to the crisis of refugees in 2015-2017. The problem of this research stems from the peak of the refugee crisis in the European Union especially Hungary itself. Hungarian Government try to take a decisive steps in dealing with the flow of refugees. The Hungarian government told that the presence of refugees can create a security threat, both from the threat of identity of Hungarian citrizen and the threat of terrorism. To analyze Hungarian policy towards the refugee crisis, the author applies the concept of Negative Human Security by Raquel Freitas. To achieve this aim, the type of research that the author used was descriptive, which of the collecting data technique used was through the literature review (library research). Furthermore, to analyze the data was applying the qualitative data analysis technique method. Keywords : Refugee Crisis, Hungarian Government, Policy, Negative Human Security.